Transfer Printing Process of Bio-Based Nylon 56 and Cotton Interwoven Fabrics - Chu, Runshan; Zhang, Yanbo; Li, Ling; Xing, Tieling; Chen, Guoqing (Journal of Composites and Biodegradable Polymers, 2023)
Using Annosol Reactive Blue DS dye as the colorant, an inkjet printing ink was developed, and its rheological properties and dynamic surface tension were evaluated for its use in dry heat transfer printing of patterns on bio-based nylon 56 and cotton interwoven fabrics. In particular, the effects of the dry heat transfer printing parameters on the printing properties of the ink on bio-based nylon 56 and cotton interwoven fabrics were investigated. The results revealed that the optimal parameters of the dry heat transfer printing of the custom-produced ink on bio-based nylon 56 and cotton interwoven fabrics are as follows: hot pressing at 130 °C under 3MPa pressure, steamer at 102 °C, and saturated steaming for 15min. The color fastness to both soap wash and rubbing of the bio-based nylon 56 and cotton interwoven fabrics dyed with Annosol Reactive Blue DS through dry heat transfer printing were determined to be of grades 3–4 and above, meeting the color fastness requirements of printed fabrics.